2016
DOI: 10.1080/15213269.2016.1142378
|View full text |Cite
|
Sign up to set email alerts
|

The Role Behavioral of Activation and Inhibition in Explaining Adolescents’ Game Use and Game Engagement Levels

Abstract: According to Gray's reinforcement sensitivity theory, variations in the functioning of two neuropsychological systems, the behavioral approach (BAS) and inhibition (BIS) system, can result in individual differences in personality. Several studies have looked at associations between personality and media use but media research integrating BAS and BIS is scarce. The current cross-sectional survey study (n = 1016) representative for Belgian adolescents investigated associations between BAS and BIS and game use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Furthermore, knowing that BIS/BAS scores can consistently be interpreted between boys and girls can help future research to scrutinize the influence of PS and RS in behaviors and conditions in which gender differences are prevalent, for example, game behavior (e.g., Vangeel et al, 2017), eating behavior (e.g., de Cock et al, 2016), weight and body composition (e.g., De Decker, Verbeken, Sioen, Moens, et al, 2017; Verbeken et al, 2012), or mental health (e.g., Bijttebier et al, 2009; Vervoort et al, 2010), also including childhood internalizing (e.g., anxiety) and externalizing (e.g., ADHD; Martel, 2013a) disorders (e.g., Martel, 2013b; Quay, 1988). Unfortunately, MI studies of the BIS/BAS scales up until now are limited to studies with community samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knowing that BIS/BAS scores can consistently be interpreted between boys and girls can help future research to scrutinize the influence of PS and RS in behaviors and conditions in which gender differences are prevalent, for example, game behavior (e.g., Vangeel et al, 2017), eating behavior (e.g., de Cock et al, 2016), weight and body composition (e.g., De Decker, Verbeken, Sioen, Moens, et al, 2017; Verbeken et al, 2012), or mental health (e.g., Bijttebier et al, 2009; Vervoort et al, 2010), also including childhood internalizing (e.g., anxiety) and externalizing (e.g., ADHD; Martel, 2013a) disorders (e.g., Martel, 2013b; Quay, 1988). Unfortunately, MI studies of the BIS/BAS scales up until now are limited to studies with community samples.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous findings which have suggested that variation exists between sexes due to differences in their use of smartphone content, as well as the fact that females have been shown to prioritize social interaction and online shopping in their smartphone use while males are more likely to play games and watch videos (Desola et al, 2016). Meanwhile, males are exposed to more violent games or videos and are thus more likely to exhibit higher levels of aggressive behavior than females (Vangeel et al, 2017). Therefore, males with high psychoticism are also more likely to relieve their stress through playing violent games than females with high psychoticism, thus increasing the possibility of smartphone addiction and resulting in a stronger relationship between smartphone addiction and psychoticism in males than females.…”
Section: Significant Moderatorsmentioning
confidence: 99%
“…Gray's reinforcement theory describes differences in personality based on two systems grounded in behavior and brain functioning: the Behavioral Inhibition System (BIS) promoting inhibition and the Behavioral Approach System (BAS) promoting approach (Gray, 1970). Past studies showed that the BIS/BAS were related to inhibitory control measured with the SST (Avila & Parcet, 2001) and violent game use in adolescents was negatively related to the BIS and positively related to the BAS (Vangeel et al, 2016). Therefore, future studies could focus on the BIS/BAS as a perhaps more relevant control variable for inhibitory control than trait aggressiveness.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%